Corporate Social Responsibility (CSR) & Its Implementation towards Good Governance (International Journal of Scientific Research and Management (IJSRM), 2017)
We are living in a world surrounded with numerous problems related to environment and society. CSR (Corporate Social Responsibility) is a means to sort out these problems to some extent because business is a part of society. Any contribution towards welfare of society is called as Corporate can no longer limit them in using resources of society and they have to be socially responsible corporate citizens and must also contribute to the social good. Corporate Social Responsibility is now accepted as a means to achieve sustainable development of an organization. In the present time, CSR has become a significant sector of modern corporate research theory and the growth of activities related to CSR in all over the world is remarkable. According to Company Act, 2013, those companies which are within the domain of section 135 of Companies Act 2013 must spend 2% of their net profits towards CSR, in the fields as specified under schedule VII, which made Indian companies to consciously work towards CSR. This research paper is based on the hypothesis, Compliance of provision relating to CSR under section 135 of the Companies Act 2013 & Companies (Corporate Social Responsibility Policy) Rules, 2014, both in letter and spirit would provide a way for Corporates, to achieve Corporate Sustainability, through promoting Good Governance to all stakeholders with in the society, in which they or their business activities are running.